Entrepreneurial learning from failure and reentry intention: the role of emotion regulation - Asif, Iqbal; Mahani, Mohammad Abdu Shakur; Subhan, Shahid; Sharizal, Hashim (Emerald Publishing Limited, 2026)
Purpose – This study aims to explore the role of psychological attributes, including self-efficacy, resilience and locus of control, for entrepreneurial learning from failure, which in turn leads to entrepreneurial reentry intentions. In addition, this study theorizes that emotion regulation moderates the relationship between entrepreneurial learning from failure and reentry intention. Design/methodology/approach – The data were collected from 318 entrepreneurs in Pakistan who had experienced business failure. The collected data were analyzed using partial least squares structural equation modeling. Findings – The results suggest that psychological attributes (self-efficacy, resilience and internal locus of control) positively relate to entrepreneurial learning from failure, which in turn influences reentry intention. Furthermore, emotion regulation positively moderates the relationship between entrepreneurial learning from failure and reentry intention. Practical implications – Entrepreneurs should perceive failure not as the end of their entrepreneurial endeavors but as an opportunity to acquire knowledge and explore other entrepreneurial pursuits. This study equips entrepreneurs, educators and policymakers with valuable insights and strategies for navigating the entrepreneurial landscape. Originality/value – This study contributes to the literature on entrepreneurial failure and reentry intention by theorizing and empirically demonstrating that psychological attributes serve as key enablers of the learning curve. In addition, this study theorizes emotion regulation as a crucial catalyst, strengthening the relationship between learning from failure and reentry intention.